Scientific justification for the selection of vegetable crops of the cruciferous family for the design of functional dairy products - Peysakhov Mark; Dunchenko Nina; Yankovskaya Valentina (BIO Web of Conferences, 2024)
This article is devoted to the study of the possibility of using domestic vegetable crops of the Cruciferous family (white cabbage, cauliflower, broccoli, kohlrabi, Brussels sprouts, red cabbage, Savoy cabbage, Chinese cabbage and turnip) as a source of essential food components based on the results of analysis of the nutrient composition. New data were obtained on the content of basic nutrients, water- and fat- soluble vitamins, micro- and macroelements and amino acids in samples of vegetable crops of the Cruciferous family. It was found that the highest content of protein and carbohydrates was observed in samples of Brussels sprouts (3.4 and 3.4%), broccoli (2.8 and 8.9%) and cauliflower (1.9 and 4.9%). It was found that the largest amount of vitamins is contained in Brussels sprouts and broccoli. According to the results of the amino acid composition of broccoli samples, it is distinguished by a variety of essential and non-essential amino acids with increased content in accordance with daily consumption standards: methionine 0.04 (2.1%), cystine 0.03 (1.6%), phenylalanine 0.12 (2.7%), aspartic 0.33 (2.7%), glutamine 0.4 (4.0%); glycine 0.09 (2.5%), serine 0.12 (1.5%). The research results obtained show the possibility of increasing the nutritional value of dairy products by adding cruciferous vegetables to expand the range of dairy products enriched with functional food ingredients. In particular, the choice of broccoli and Brussels sprouts for designing technology and modeling the composition of new dairy products with functional ingredients was scientifically justified. The data obtained allow us to consider vegetable products of the Russian agro- industrial complex as raw materials rich in essential food ingredients when creating new competitive dairy products.